2010
DOI: 10.1105/tpc.109.066423
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis rcn1-1 Mutation Impairs Dephosphorylation of Phot2, Resulting in Enhanced Blue Light Responses  

Abstract: Phototropins (phot) sense blue light through the two N-terminal chromophore binding LOV domains and activate the C-terminal kinase domain. The resulting phototropin autophosphorylation is essential for biological activity. We identified the A1 subunit of Ser/Thr protein phosphatase 2A (PP2A) as interacting with full-length phot2 in yeast and also interacting with phot2 in an in vitro protein binding assay. Phenotypic characterizations of a phot1-5 rcn1-1 (for root curling in n-naphthylphthalamic acid1) double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 52 publications
2
73
0
Order By: Relevance
“…4C) contained the protein phosphatase 2A regulatory subunit A3 (PP2AA3). Mutants of PP2A subunits or PP2A-associated regulatory proteins such as TAP46 have altered metabolism and responses to ABA and environmental signals (Kwak et al, 2002;Luo et al, 2006;Tseng and Briggs, 2010;Ahn et al, 2011). We found that pp2aa3 T-DNA mutants had increased Pro accumulation (Fig.…”
Section: Additional Genes With Previously Unknown Effects On Pro Accumentioning
confidence: 73%
See 1 more Smart Citation
“…4C) contained the protein phosphatase 2A regulatory subunit A3 (PP2AA3). Mutants of PP2A subunits or PP2A-associated regulatory proteins such as TAP46 have altered metabolism and responses to ABA and environmental signals (Kwak et al, 2002;Luo et al, 2006;Tseng and Briggs, 2010;Ahn et al, 2011). We found that pp2aa3 T-DNA mutants had increased Pro accumulation (Fig.…”
Section: Additional Genes With Previously Unknown Effects On Pro Accumentioning
confidence: 73%
“…Likewise, the effect of pp2aa3 on Pro accumulation could be either direct or indirect. Of the three genes (RCN1, PP2AA2, and PP2AA3) encoding PP2A regulatory A subunits in Arabidopsis, RCN1 has the dominant role in regulating several hormone and developmental responses (Kwak et al, 2002;Larsen and Cancel, 2003;Zhou et al, 2004;Blakeslee et al, 2008;Tseng and Briggs, 2010), with relatively little function detected for PP2AA3. This may suggest a more specific role of PP2AA3 in Pro metabolism or stress response.…”
Section: Gwas Identifies Genes Connecting Pro Accumulation To Cellulamentioning
confidence: 99%
“…Various stimuli can lead to stomatal closure, but stomatal opening is predominately evoked by means of wavelength-responsive mechanisms 27 . The regulatory mechanism of stomatal opening by blue light has been well studied in a number of C 3 plants 28,29 , but its role is less clear in CAM plants 30 light-induced switch from C 3 to CAM in Clusia minor 31 . In the present study, we observed a light-induced gene expression profile for a blue/UV-A light-absorbing cryptochrome 2 (CRY2) (Aam348626) that has been implicated in inhibition of hypocotyl elongation, regulation of flowering time and entrainment of the circadian clock 32 .…”
mentioning
confidence: 99%
“…To further determine the role of CYCH;1 in blue light-induced stomatal opening, we assessed the expression of genes involved in this process, such as MYB60 (Cominelli et al, 2005), MYB61 (Liang et al, 2005), HRB1 (Sun et al, 2012), PP7 (Sun et al, 2012), RPT2 (Inada et al, 2004), RCN1 (Tseng and Briggs, 2010), and 14-3-3 (Kinoshita et al, 2003), in the cych;1 RNAi mutants and wild-type controls using qRT-PCR. No significant changes in the expression levels of these genes were found, indicating that CYCH;1 does not affect blue light-induced stomatal opening by regulating the transcription of these genes (Fig.…”
Section: Downstream Targets Of Cych;1mentioning
confidence: 99%
“…PHOT1-mediated stomatal opening depends on the interaction between Root Phototropism2 (RPT2) and PHOT1 (Inada et al, 2004). On the other hand, Root Curling in N-naphthylphthalamic acid1 (RCN1), the A1 subunit of Arabidopsis (Arabidopsis thaliana) protein phosphatase2A (PP2A), interacts with and dephosphorylates PHOT2 (deactivation) to inhibit PHOT2-mediated stomatal opening (Tseng and Briggs, 2010). H + -ATPase functions downstream of PHOT-mediated stomatal opening.…”
mentioning
confidence: 99%